MENUMBUHKAN HARAPAN DAN MEMELIHARA OPTIMISME : STUDI PSIKOLOGI POSITIF - Aprillia Salnabila; Cindi Indriani, Elicia Yolanda, Yemima Priscila Barutu, Zahra Khairunnisa (ADISAM PUBLISHER, 2025)
Hope and optimism are defined as moods or attitudes associated with positive expectations about the future, involving a belief that good things will happen frequently. Experts such as Peterson and Seligman define both as behaviours directed towards achieving desired outcomes. Hope helps individuals find meaning in life, cope with challenges, and foster positive relationships. Individuals with high hope tend to view stress as a challenge, are motivated to seek solutions, and take action in the face of uncertainty. Optimism, as a positive mental attitude, is considered important in shaping healthy and productive mindsets, enabling individuals to rise from despair and see failure as temporary